Optimizing NBE PK/PD assays using the Gyrolab Affinity Software; conveniently within the bioanalyst's existing workflow. (16th February 2018) - Myzithras, Maria; Bigwarfe, Tammy; Waltz, Erica; Li, Hua; Ahlberg, Jennifer; Rybina, Irina; Low, Sarah; Kenny, Cynthia Hess; Miglietta, John; Kroe-Barrett, Rachel
Aim: The fully automated microfluidics-based Gyrolab is a popular instrument for the bioanalysis of protein therapeutics; requiring minimal sample and reagent volumes. Gyros offers affinity software for determining binding affinity in solution using a high-throughput method and miniaturized reactions.Results: Using this affinity software, multiple CTGF-targeting reagents were characterized on the Gyrolab after <100% target coverage was seen in a cynomolgus pharmacokinetic/PD study dosed with anti-CTGF antibodies. The results uncovered magnitude differences in binding affinities between the dosed antibody, target and assay reagents.Conclusion: The binding affinity values were used to investigate reduced target coverage and results highlight potential of the affinity software for incorporation into the bioanalyst's existing Gyrolab workflow for characterizing reagents and optimizing pharmacokinetic/PD bioanalytical assays.